Will Skill-Based Immigration Policies Lead to Lower Remittances? An Analysis of the Relations between Education, Sponsorship, and Remittances - Sankar Mukhopadhyay; Miaomiao Zou (Institute of Labor Economics (IZA), 2018)
As more and more developed countries adopt policies that favor highly educated immigrants, the impact of such policies on developing countries remains unclear. Some researchers have argued that migrants who are more educated tend to bring their immediate family members to the host country, and thus, send less money to the source country in remittances. While there is numerous papers documenting association between education and remittance, whether that is related to sponsorship decision remains under-explored. Using individual level panel data from the New Immigrant Survey, we show that sponsoring family members leads to lower remittance. Furthermore, we show that college educated immigrants from high-income families are less likely to sponsor relatives, presumably because of relatively higher opportunity cost of migration of their relatives. Together, these two results suggest a positive association between education and remittances, which is indeed, what we find in the data. Our extended analysis shows that alternative explanations (such as higher income of more educated immigrants, or repaying implicit educational loans) cannot completely explain the positive association between education and remittances. Our results suggest that skill-based immigration policies are likely to result in more remittances.
Keywords: O15; F22; F24; J61; 330; immigration; remittance; sponsorship; education